Kajian Astronomi Tradisional (Palelintangan) Di Lombok Nusa Tenggara Barat / I Wayan Rupa, dkk. ; Penyunting : Aditya Pratama - I Wayan Rupa; Ni Luh Ariani; Ida Bagus Sugianto; Aditya Pratama (Ombak, 2014)
xiv + 153 hlm. ilus. 21 cm.